The Effect of Cochlear Size on Cochlear Implantation Outcomes. (4th June 2019) - Kuthubutheen, Jafri; Grewal, Amandeep; Symons, Sean; Nedzelski, Julian; Shipp, David; Lin, Vincent; Chen, Joseph
Abstract : Objectives. To determine if cochlear duct length and cochlear basal diameter, measured using routinely available radiology software, affect hearing outcomes after cochlear implantation with two different length electrodes. Methods. 55 patients who received a Med-El Flex electrode were retrospectively reviewed. 34 patients received the Flex 31 electrode (31mm) and 21 patients received the Flex 28 electrode (28mm). Preoperative high-resolution CT scans of the temporal bone were reformatted in the axial and coronal plane. The basal diameter of the cochlear (A-value) and the outer-wall lengths of the cochlear duct were measured using readily available imaging software. Postoperative plane X-rays were used to determine the degree of electrode insertion and the number of electrodes within the cochlea and speech discrimination scores at 6 months were evaluated. Results . The cochlear metrics obtained were comparable with those previously published in the literature. There was no significant difference in the degree of insertion or speech outcomes between the two electrode lengths. However, when the group who had received the shorter electrode were analysed, there was an association seen between both cochlear duct length and cochlear diameter and speech outcomes. Conclusions. Cochlear size may be a factor in determining speech outcomes that cannot be explained solely by insertion depth or degrees of insertion. Further studies are required to determine if cochlear duct length is an independent predictor of speech outcomes.